2015
DOI: 10.1007/s00125-014-3487-2
|View full text |Cite
|
Sign up to set email alerts
|

Haptoglobin genotype modulates the relationships of glycaemic control with cognitive function in elderly individuals with type 2 diabetes

Abstract: Aims/hypothesis The purpose of this study was to investigate whether the association of glycaemic control with cognitive function is modulated by the haptoglobin 1-1 (Hp 1-1) genotype in cognitively normal elderly with type 2 diabetes. Methods In this cross-sectional study, we examined 793 participants who were genotyped for Hp (80 Hp 1-1 carriers and 713 Hp 1-1 non-carriers) enrolled in the Israel Diabetes and Cognitive Decline (IDCD) study. Glycaemic control was operationally defined by HbA1c level. The ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 50 publications
1
13
0
Order By: Relevance
“…We found that Hp 2 carriers have a 30% lower risk for larger carotid plaque volume compared to Hp 1-1 carriers. These results are consistent with recent literature of associations of Hp 1-1 with cerebrovascular disease 8,25 . In contrast, we did not nd signi cant associations between Hp phenotype and cIMT, carotid distensibility and elastography measures.…”
Section: Patient Characteristicssupporting
confidence: 93%
“…We found that Hp 2 carriers have a 30% lower risk for larger carotid plaque volume compared to Hp 1-1 carriers. These results are consistent with recent literature of associations of Hp 1-1 with cerebrovascular disease 8,25 . In contrast, we did not nd signi cant associations between Hp phenotype and cIMT, carotid distensibility and elastography measures.…”
Section: Patient Characteristicssupporting
confidence: 93%
“…Carotid atherosclerosis was reported to be associated with an increased risk of stroke and poorer cognitive performance in the elderly [ 44 ]. In addition, patients with the Hp 1-1 genotype were identified to have an increased risk of stroke in a longitudinal study of type 1 diabetes and poorer cognitive function in elderly individuals with type 2 diabetes [ 45 , 46 ]. The influence of Hp genotypes on stroke might be partly attributed to their association with carotid atherosclerosis, which appears to have a different aetiology than that of coronary artery disease.…”
Section: Discussionmentioning
confidence: 99%
“…Serum was extracted from blood samples, and Hp genotypes were determined by polyacrylamide gel electrophoresis from 10 μL of plasma using established methods ( 14 ) and dichotomized as Hp 1-1 carriers versus Hp 2-1 or Hp 2-2 carriers. We chose to use the dichotomy of Hp 1-1 carriers versus others because we found no difference between the Hp 1-2 and Hp 2-2 carriers in our prior studies assessing the association of Hp with cognition ( 11 , 12 ). Demographic details and T2D-related characteristics including longitudinal glycemic control based on repeated HbA 1c levels, systolic and diastolic blood pressure, LDL, HDL, total cholesterol, and creatinine were available for all participants.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, the association of glycemic control with cognitive function was primarily observed for individuals with Hp 1-1 but not for Hp 1-2 and Hp 2-2 carriers. These findings suggest that individuals with the Hp 1-1 genotype may be more susceptible to the deleterious effects of poor glycemic control ( 12 ). We examined the interrelationship of Hp genotype, HbA 1c levels, and regional volume of the hippocampus obtained from MRI of the brain in older individuals with T2D.…”
Section: Introductionmentioning
confidence: 99%